MANAJEMEN PIUTANG PADA HARRIS HOTEL SENTRALAND SEMARANG - Albert Filbert; Vincentia Devina Setyawati (ICMA Nasional, 2024)
This research aims to determine the turnover of receivables at Harris Hotel Sentraland Semarang. The data collection technique used is to collect data by using reports contained in the company. The data analysis technique used is qualitative methods. The percentage of receivables paid, from 2021 to 2022, decreased by 0.79%. Likewise, the percentage of outstanding receivables at the end of 2022 decreased by 0.27%. Regarding the level of receivables turnover, it can be seen from mathematical calculations that the turnover that occurs shows that in 2021 it will occur 9 times and in 2022 it will occur 4 times. The average collection of receivables shows good things for the company, in 2021 the Average Collection Period points to 41 days while in 2022 it points to 86 days. This happened faster than the company policy which requires 180 days